Techno-economic study on extended-range electric vehicles: with internal combustion engine and micro-gas turbine - Tan, Qingyu (Nanyang Technological University, 2023)
With the growing concern on fossil fuel displacement and environment protection, the adoption of electric vehicle is a crucial means to clean energy transport. In an Asian urban environment, traditional automotive is very inefficient operating in such driving patterns. Electric powertrain is a viable substitute for heat engine powertrain for its efficiency and low energy cost. However, BEV, which only utilize grid power, will induce too much cost on the consumer and the limited infrastructure. Hence the “range anxiety” and limited infrastructure of electric vehicles would diminish the incentive of Asian consumers to purchase such vehicles. To solve the range limitation of electric vehicle, a low power range extender can be helpful in long-range driving occasions. According to the need of Asian consumers of vehicles, a multi attribute economic analysis is conducted to compare the utilities for consumer at same price level. The analysis showed EREV powertrain would provide very similar utility for consumers while BEV’s utility is limited by its range and charging network. This study analyzes the advantages and drawbacks of two types of range extender: Internal Combustion Engine and Micro-Gas Turbine. A compact sedan model is examined in Singapore context and the lifetime cost of the vehicle is calculated. Compared to BEV, EREV would have significantly lower initial cost and operates 70% of its annual mileage on grid power. The savings of battery cost and fuel cost made EREV a promising configuration for EVs’ large-scale adoption. However, the optimal range extender can be different for each types of vehicles. With similar power-to weight ratio, MGT would have a much lower power-to-volume ratio, which made it suboptimal for small urban sedan.